Screening of antioxidant property of Eclipta alba - Mittal, Rohit; Kumar, R; Chahal, HS (Journal of Drug Delivery and Therapeutics, 2018)
The aim of the study was to examine the possible antioxidant activities of the methanolic extracts of medicinal plants, Eclipta alba. We examined for such properties such as nitric oxide radical scavenging assay, DPPH radical scavenging activity. Free radicals are atoms or molecules that have one or more unpaired electrons on its outer orbital, highly reactive, and could damage cell inside human body. Human body produce antioxidant to neutralize free radicals, but human ageing and stress oxidative conditions would increase the formation of free radicals, therefore an exogenous antioxidant are needed. Asteraceae is the largest family among the plant kingdom, therefore it has a great potential as source of exogenous antioxidant. The flavonoid content of the plant extract was estimated by the method of (Lamaison and Carnat, 1990). Briefly 1.0 ml of plant extract was mixed with 1.0 ml of aluminium chloride reagent and resultant colour was read at 430 nm. The flavonoid content of the extract was expressed as mg quercetin equivalent/gm dry wt. of extract. The coarsely powdered plant materials of Eclipta alba (2000 g) were extracted separately to exhaustion in Soxhlet apparatus for 72 hours by using methanol solvent The crude extract was filtered using 125 mm Whatman® qualitative filter paper under sterile condition. A methanol solution of the sample at various concentrations was added to 0.5 ml of 0.1 mM methanolic solution of DPPH and allowed to stand for 30 min at 25°C in darkness. The absorbance of the sample was measured at 517 nm. A 0.1 mM solution of DPPH in methanol was used as control, whereas ascorbic acid was used as reference standard. The absorbance of the pink chromophore formed during the diazotization of the nitrite with sulphanilamide and the subsequent coupling with naphthyl ethylenediamine dihydrochloride was measured at 546 nm. The percentage of inhibition of the extract shown 39% in 25µg and in 100µg it was 73 percent.